Penerapan Metode Crm (Customer Relationshipmanagement) Pada Divisi Pelayanan Teknis Barat Di Pdam Surya Sembada Kota Surabaya - Muhammad Niqey Dzi Qolbin Saliem; Enny Aryanny (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
PDAM Surya Sembada Kota Surabaya is a regionally owned water company which operates in the field of production and services for the community. In serving the community, customers often complain that they are dissatisfied with the quality of service in the West Technical Services division. This is because they have not implemented a customer approach system. This research aims to minimize the occurrence of incoming customer complaints. CRM (Customer Relationship Management) is a method that can be used to minimize customer complaints by approaching customers, explaining customer dissatisfaction with services clearly and politely and providing the best solution to resolve the problem. This method creates a solution where customer complaints about service quality are reduced and makes it easier for the field team to find customer addresses.